Statistical learning for biomedical data - Malley, James D. Malley, Karen G. Pajevic, Sinisa (Practical guides to biostatistics and epidemiology, 2011)
This book is for anyone who has biomedical data and needs to identify variables that predict an outcome, for two-group outcomes such as tumor/not-tumor, survival/death, or response from treatment. Statistical learning machines are ideally suited to these types of prediction problems, especially if the variables being studied may not meet the assumptions of traditional techniques. Learning machines come from the world of probability and computer science but are not yet widely used in biomedical research.